The Influence of Online Customer Review and Content Marketing on Purchasing Decision for Jiniso Products in the Tiktok Application - Siti Rohmah Komala; Salsabila Rahma; Siti Nurnaningsih; Lis Tatin Hernidatiatin (Indonesian Journal of Business Analytics, 2024)
The aim of this research is to evaluate the impact of content marketing and Online Customer Reviews on Jiniso purchasing decisions on the TikTok Shop application. The research population consisted of 120 people, all of whom were TikTokShop users in Cirebon. The examination in this study was carried out with the help of Smartpls. The study finding that content marketing and Online Customer Reviews work together to influence TiktokShop buyer decisions is clearly visible here. Consumers rely heavily on online reviews when making purchases on the TikTokShop marketplace. In making purchases on the TikTokShop marketplace, content marketing plays a major role. Next, we can find Online Customer Reviews and the best content marketing factors to test purchasing decisions by using reliability testing in Partial Least Squares (PLS) analysis using Cronbach Alpha, Composite Reliability, and Avarage Variance Extracted (AVE) techniques. Two factors probably account for 67.6% of the variance in purchasing decisions (R Squared = 0.676). The research results show that the model makes a significant contribution to understanding the variables that influence consumer purchasing decisions.